Influence of Carbon Content on Elevated Temperature Fatigue Properties of Different Steel Alloys - Hessen J. Mohamed Alalkawi; Thabat. M. Ali; N.M. Abdulmuhssan; kiffaya Al-saffar (Engineering and Technology Journal, 2012)
Fatigue properties (fatigue life and fatigue limit) of three different carbon content steel alloys, CK35, Y8 and Y10 were investigated at RT and 300 ºC fatigue testing. The main contribution of this work was to find the influence of carbon content on high temperature fatigue properties. It was found that the fatigue life in both cases, RT and 300 ºC, decreased dramatically via increasing carbon content from 0.35% to 0.8% but at 1% carbon content the fatigue life was increased. The fatigue limit and its reduction percentage took the same trend of the fatigue life.